Bumba-meu-boi do Maranhão: uma reflexão etnomusicológica sobre sustentabilidade musical - Souza, Thiago Costa de (2010)
This work seeks to present a study on musical practices in Brazilian culture from the perspective of musical sustainability. To define the object of study, research was carried out on the trajectory of the Bumba-meu-boi do Maracanã group since the beginning of the 21st century. The focus of this study is on the sustainable aspects that helped maintain this group throughout this period. Therefore, this work's main objective is to understand the historical trajectory of Bumba-meu-boi do Maracanã over the last twenty-five years, seeking to understand, based on studies on musical sustainability, which are the important points for maintaining its own existence. The set of studies on musical sustainability suggests that sociocultural, environmental, political and economic changes are inevitable and seeks to manage these changes to guarantee the integrity and continuity of musical manifestations in the future. Furthermore, the main authors of these studies suggest that discussions and actions around musical sustainability should be guided by ecological principles and not economic ones. In this sense, the ecosystem view, originating from ecological studies, has as its principle observing the complex organism interacting with broader physical factors, which form the environment or biome to which they belong. At this point, we cannot separate the organism from the environment. Therefore, one of the perspectives that studies on musical sustainability have to offer is to think of music as a musical ecosystem. In this research, nine concepts were worked on in search of a contextual, holistic and multi-scale vision to guide the process of analyzing this musical manifestation. Methodologically, this is a qualitative research of a basic nature, which uses the historical procedure method as a technical means, structured through bibliographic and documentary research, combined with ethnographic procedures such as participant observation and interviews. The results obtained indicate that the Boi de Maracanã is maintained through: faith and the syncretic aspects in which popular Catholicism and the enchantment of the mine drum coexist, in search of the survival of the human being as part of an ancestral symbolic universe; the community census and belonging to a ritualistic cycle that gives meaning to life; the ancestry and continuity arising from the Afro-indigenous worldview; its resilient power to restructure and dialogue with the public and private sector in search of financial survival; constant learning, which reacts to the disturbances of the contemporary world, such as in the period of social isolation; and the association of individuals and the use of their skills in search of collective satisfaction. Therefore, understanding sustainable paths based on an ecosystemic perspective throughout this historical period is important to understand the process of continuity of the Maracanã Boi and its current state. In this sense, being together making music is one of the crossroads where the various dimensions connect in the physical, philosophical, religious and transcendental sense.